Navigating The Cashless Shift: A TAM-Based Qualitative Inquiry into Accounting Students Adoption Of DANA - Ayu Safitri; Rahayu Indriasari; Muhammad Ilham Pakawaru; Andi Ainil Mufidah Tanra (SAFE-Network, 2026)
This study investigates the adoption of DANA as a primary digital payment platform among accounting students at Tadulako University. The primary objective is to analyze how Perceived Usefulness and Perceived Ease of Use determine student acceptance of financial technology using the Technology Acceptance Model (TAM) framework. The research method employs a descriptive qualitative approach designed to explore a deep understanding of user behavior. Data were gathered through in-depth, semi-structured interviews with informants selected via purposive sampling, specifically active students who are regular users of the DANA application. The data analysis process included stages of data reduction, systematic data display, and verification to ensure the validity of findings regarding students' transactional experiences. The results reveal that students attribute high functional value to the platform due to accelerated transaction processing, time optimization, and enhanced security features. Additionally, the streamlined registration process and minimalistic interface significantly reduce technical barriers for novice users. This study concludes that the perceived simplicity of the interface acts as a catalyst that reinforces the perceived functional benefits, ultimately driving widespread adoption of DANA for cashless transactions within the academic environment in accordance with TAM postulates.